The Implementation of Hypnoteaching Methods to Improve Good Learning Attitude in Thematic Learning - Hikmah, Shofiatul; Lessy, Zulkipli (Indonesian Journal of Multidisciplinary Educational Research, 2024)
This research was initiated by the problem of learning attitudes in class IV MIN 1 Bantul students, which were not conducive. This caused the delivery of thematic material not entirely accepted because many students still talk to themselves, play alone, and often even have permission to go to the bathroom. The research aimed to determine the improvement of learning attitudes that were initially not conducive to good learning attitudes using the hypnoteaching method. This study used a qualitative method. Researchers use data from various sources, such as interviews, questionnaires, and documentation. This research was carried out on class IV students of MIN 1 Bantul. The implementation of hypnoteaching that teachers carried out was using positive suggestion sentences spoken by the teacher and followed by students as in the following example sentences: "I am a good child, I can listen to lessons well, I will receive knowledge in a good way," and so on. The condition of students who initially had poor learning attitudes, after applying the hypnoteaching method, was that students could be controlled so that they gave rise to good learning attitudes and could receive the material as a whole.